Impact of Institutional Risk Management, Technological Adoption, and Climate Change Adaptation on Ghana’s Crop Productivity - Hewlett, Dexter Senanu Kofi; Tee, Evans; Essel-Mensah, Kojo; Asabre, Janet (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study investigated the impact of Agricultural Technology Adoption (ATA), Climate Change Adaptation Measures (CCAM), and Institutional Risk Management (IRM) on crop production (CP). The purpose of this study is to assess how these variables influence agricultural productivity and identify the key drivers of successful crop production in the context of climate change and institutional challenges. A quantitative research design was employed utilising survey data collected from farmers across different agricultural regions. Structural equation modelling (SEM) was used for data analysis to examine the relationships between ATA, CCAM, IRM, and CP. The findings indicated that ATA, CCAM, and IRM had a positive and statistically significant effect on crop production. This study highlights that adopting advanced technologies, implementing effective climate change adaptation strategies, and strengthening institutional risk management can significantly enhance crop productivity. This study contributes to the literature by emphasising the importance of technological adoption and risk management strategies in agriculture. These practical implications suggest that policymakers should prioritise the integration of ATA and IRM into agricultural policies to promote sustainable and resilient agricultural practices, thereby improving overall crop production and food security.